Union Therapy-An Urgent Need to Health Care for Covid and Future Threats - Kala, Kanishk; Sodhi, Rupinder Kaur (Journal of Pharmacy Practice and Community Medicine)
Human suffering through infections is inevitable. History has witnessed drastic negative impacts of infectious plagues which were primarily managed through prayers and latter through medicines. In spite of high technology at present COVID-19 and other resistant infections and diseases still pose a threat to global health and still is unchecked. Thus to combat it a modality Union therapy is conceptualized which synergistically uses the past and present medical techniques to cope up the COVID. It tries to merge the positive effects of supernatural medicine with modern medicine to make therapy comprehensive complete in all aspects. This effort would help to cope up new emerging diseases like COVID and in cases of palliative care where psychological aspects and the patient’s religious and spiritual needs play a role. Overall it will help to frame a bridge between past and present treatment modalities by scientifically assessing and merging the objective similarities in them. It will help to foster new areas and make therapy acceptable and accessible to a wide range of global population.
Keywords: Union Therapy; COVID-19; Holistic Medicine; Integrative medicine; Mytho scientific